The Library of the Future: A Scenario-based Approach. Issue 1 (2nd January 2023) - Oliver, John; Reid, Martin; Gray, Katy
Abstract: The changing dynamics, uncertainties, and operating environments of many library services across the globe make it difficult for leadership teams to develop strategic plans. This article presents empirical findings on a scenario-planning project that sought to develop a mission, vision and strategy for the House of Commons Library Service in UK Parliament. Set in the context of a major £6bn Restoration and Renewal program, it demonstrates how Scenario Planning was used to manage significant levels of uncertainty and develop a long-term strategic direction that sought to deliver high-quality Library Services provision over the next 10 years.